Rust and bone [videorecording (DVD)] - Audiard, Jacques; Cotillard, Marion, 1975-; Schoenaerts, Matthias, 1977-; Verdure, Armand (Sony Pictures Home Entertainment, 2013)
Ali and his son depart Belgium for Antibes to reside with his sister and her husband. Ali's connection with Stephanie, a killer whale trainer, intensifies when she endures a horrific accident.